Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1126/science.aax0504
|View full text |Cite
|
Sign up to set email alerts
|

Old carbon reservoirs were not important in the deglacial methane budget

Abstract: Permafrost and methane hydrates are large, climate-sensitive old carbon reservoirs that have the potential to emit large quantities of methane, a potent greenhouse gas, as the Earth continues to warm. We present ice core isotopic measurements of methane (Δ14C, δ13C, and δD) from the last deglaciation, which is a partial analog for modern warming. Our results show that methane emissions from old carbon reservoirs in response to deglacial warming were small (<19 teragrams of methane per year, 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 99 publications
4
37
0
Order By: Relevance
“…Radiocarbon ( 14 C) based studies in Yedoma regions have shown that pre-aged C is highly vulnerable to microbial decomposition to CO 2 when released into streams [12][13][14] , while studies targeting thermokarst lakes (formed from abrupt thaw processes) detected CH 4 emissions as old as 42,900 years before present (yBP) 15 . In contrast, contemporary C dominated emissions to the atmosphere in non-Yedoma permafrost regions 6,7,16,17 , and ice-core studies suggest it is unlikely that large-scale emissions of pre-aged CH 4 from permafrost regions have occurred in the past~15,000 years 18 . It therefore remains unclear whether the release of preaged permafrost C into inland waters is an important driver of landscape-scale C emissions relative to contemporary C turnover.…”
mentioning
confidence: 99%
“…Radiocarbon ( 14 C) based studies in Yedoma regions have shown that pre-aged C is highly vulnerable to microbial decomposition to CO 2 when released into streams [12][13][14] , while studies targeting thermokarst lakes (formed from abrupt thaw processes) detected CH 4 emissions as old as 42,900 years before present (yBP) 15 . In contrast, contemporary C dominated emissions to the atmosphere in non-Yedoma permafrost regions 6,7,16,17 , and ice-core studies suggest it is unlikely that large-scale emissions of pre-aged CH 4 from permafrost regions have occurred in the past~15,000 years 18 . It therefore remains unclear whether the release of preaged permafrost C into inland waters is an important driver of landscape-scale C emissions relative to contemporary C turnover.…”
mentioning
confidence: 99%
“…However, there is no consensus on how gas emissions from these dynamic systems fit into a climate-change scenario 20 . For example, while field observations on formerly glaciated margins point towards massive emissions of greenhouse gases following ice-sheet retreat 21 , recent analysis of ice-cores suggest that post-LGM (Last Glacial Maximum, ∼20,000 years ago) methane release from old reservoirs was too small to impact the global climate 22 . A challenging aspect on the quantification of present-day emissions is that seepage may be more widespread and abundant than we are able to identify based on the presence of gas plumes in hydro-acoustic surveys.…”
mentioning
confidence: 99%
“…Geologic ethane emissions in the modern atmosphere are estimated at 2–4 Tg year −1 (Etiope & Ciccioli, 2009). However, the importance and magnitude of geologic hydrocarbons in the preindustrial atmosphere has been heavily debated based on measurements of radiocarbon‐free methane in ice cores (Dyonisius et al, 2020; Hmiel et al, 2020; Petrenko et al, 2017).…”
Section: Atmospheric Cycling and Budgets Of Acetylene Ethane And Mementioning
confidence: 99%
“…Acetylene has a simple biogeochemical cycle, with fire as the major source during the preindustrial (see section 2.1 for global budget discussions) (Nicewonger et al, 2020; Xiao et al, 2007). Ethane has one additional source from geologic emissions, the magnitude of which is controversial (Dyonisius et al, 2020; Etiope & Ciccioli, 2009; Hmiel et al, 2020; Petrenko et al, 2017). Methane and CO are considerably more complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation